2023
DOI: 10.1371/journal.pone.0282026
|View full text |Cite
|
Sign up to set email alerts
|

A numerical simulation method for pressure drop and normal air velocity of pleated filters during dust loading

Abstract: Pressure drop is an important indicator that affects the filtration performance of the pleated filter, and the deposition of dust particles within the pleats is crucial to the evolution of the pressure drop. In this study, the pressure drop during PM10 loading process was investigated for a series of V-shaped and U-shaped filters with a pleat height of 20 mm and different pleat ratios (the ratio of pleat height to pleat width: α = 0.71–3.57). In the numerical simulations, numerical models suitable for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It has been reported that there is a relationship between pressure drop and particle removal. 71 When there is a higher pressure drop in a filtration system, it becomes more difficult for air to move through the filter. Consequently, this resistance prevents airborne particles from entering easily, acting as a protective measure to prevent the infiltration of contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that there is a relationship between pressure drop and particle removal. 71 When there is a higher pressure drop in a filtration system, it becomes more difficult for air to move through the filter. Consequently, this resistance prevents airborne particles from entering easily, acting as a protective measure to prevent the infiltration of contaminants.…”
Section: Resultsmentioning
confidence: 99%